Intrauterine levonorgestrel delivery with frameless fibrous delivery system: review of clinical experience - Wildemeersch D; Andrade A; Goldstuck ND; Hasskamp T; Jackers G (Dove Medical Press, 2017)
Dirk Wildemeersch,1 Amaury Andrade,2 Norman D Goldstuck,3 Thomas Hasskamp,4 Geert Jackers5 1Gynecological Outpatient Clinic and IUD Training Center, Ghent, Belgium; 2Centro de Biologia da Reprodução, Universidade Federal Juiz de Fora, Juiz de Fora, Brazil; 3Department of Obstetrics and Gynaecology, Faculty of Medicine and Health Sciences, Stellenbosch University and Tygerberg Hospital, Western Cape, South Africa; 4Klinik für Operativen Gynäkologie, GynMünster, Münster, Germany; 5Applied Controlled Release, Technology Park, Ghent (Zwijnaarde), Belgium Abstract: The concept of using a frameless intrauterine device (IUD) instead of the conventional plastic framed IUD is not new. Frameless copper IUDs have been available since the late 1990s. They rely on an anchoring system to retain in the uterine cavity. The clinical experience with these IUDs suggests that frameless IUDs fit better as they are thin and, therefore, do not disturb or irritate the uterus. High tolerance and continuation rates have been achieved as complaints of pain are virtually nonexistent and the impact on menstrual blood loss is minimal. Conventional levonorgestrel-releasing intrauterine systems (LNG-IUSs) are very popular as they significantly reduce menstrual bleeding and provide highly effective contraception. However, continuation of use remains problematic, particularly in young users. Total or partial expulsion and displacement of the LNG-IUS also occur too often due to spatial incompatibility within a small uterine cavity, as strong uterine contractions originate, attempting to get rid of the bothersome IUD/IUS. If not expelled, embedment ensues, often leading to chronic pain and early removal of the IUD/IUS. Several studies conducted recently have requested attention to the relationship between the LNG-IUS and the endometrial cavity. Some authors have proposed to measure the cavity width prior to inserting an IUD, as many uterine cavities are much smaller than the currently existing LNG-IUSs. A frameless fibrous drug delivery system fits, in principle, in all uterine cavities and may therefore be preferable to framed drug delivery systems. This review examines the clinical performance, acceptability, and potential of the frameless LNG-IUS (FibroPlant®) when used for contraception, treatment of heavy menstrual bleeding, dysmenorrhea, and endometrial suppression in women using estrogen replacement therapy, endometrial hyperplasia, and other gynecological conditions. The review concludes that FibroPlant LNG-IUS offers unique advantages in reducing side effects. Keywords: LNG-IUS, frameless, efficacy, safety, acceptability